2017
DOI: 10.1080/14656566.2017.1408792
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ipragliflozin in Japanese patients with type 2 diabetes in real-world clinical practice: interim results of the STELLA-LONG TERM post-marketing surveillance study

Abstract: Ipragliflozin was well tolerated and effective in Japanese patients with T2D; no new safety issues were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
29
0
3
Order By: Relevance
“…This subgroup analysis of data from the STELLA‐LONG TERM study was carried out to evaluate the impact of BMI on the efficacy and safety of ipragliflozin in Japanese type 2 diabetes mellitus patients under real‐world conditions. The results pertaining to patient background characteristics showed that patients with higher BMI had less favorable glycemic control and lipid profile, as well as higher blood pressure, estimated glomerular filtration rate, hematocrit and uric acid, than patients with lower BMI, although the clinical significance of differences in the latter three factors remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This subgroup analysis of data from the STELLA‐LONG TERM study was carried out to evaluate the impact of BMI on the efficacy and safety of ipragliflozin in Japanese type 2 diabetes mellitus patients under real‐world conditions. The results pertaining to patient background characteristics showed that patients with higher BMI had less favorable glycemic control and lipid profile, as well as higher blood pressure, estimated glomerular filtration rate, hematocrit and uric acid, than patients with lower BMI, although the clinical significance of differences in the latter three factors remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the STELLA‐LONG TERM study is available in the previous interim report. In summary, the study population comprised all Japanese type 2 diabetes mellitus patients who were first prescribed ipragliflozin between 17 July 2014 and 16 October 2015 at any of the participating medical centers in Japan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its beneficial effects on glycemic control and body weight have been demonstrated in a number of randomized, double-blind, placebo-controlled trials [8][9][10][11][12][13][14][15][16]. Since then, a post-marketing long-term study of ipragliflozin has further demonstrated its efficacy and safety in patients with T2DM [17]. While the efficacy and safety of ipragliflozin have been demonstrated in previous phase 3 trials, the majority of these trials were conducted in Asia.…”
mentioning
confidence: 99%